2019
DOI: 10.1186/s12986-019-0363-6
|View full text |Cite
|
Sign up to set email alerts
|

Whole blueberry protects pancreatic beta-cells in diet-induced obese mouse

Abstract: Background Blueberry is rich in bioactive substances and possesses powerful antioxidant potential, which can protect against oxidant-induced and inflammatory cell damage and cytotoxicity. The aim of this study was to determine how blueberry affects glucose metabolism and pancreatic β-cell proliferation in high fat diet (HFD)-induced obese mice. Methods Wild type male mice at age of 4 weeks received two different kinds of diets: high-fat diet (HFD) containing 60% fat or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 56 publications
1
28
0
Order By: Relevance
“…In contrast to ndings made in human interventions, numerous animal studies reported bene ts of blueberries alone or mixed with other berries on weight management (42)(43)(44), markers of glucose/insulin resistance or sensitivity (10,(42)(43)(44)(45)(46), lipid pro le (42,47,48), vascular health (49,50), kidney function (51) or in ammatory markers (10,(42)(43)(44)(50)(51)(52)(53). Results from studies assessing other MetS phenotype parameters have been consistent with our ndings overall.…”
Section: Discussionsupporting
confidence: 87%
“…In contrast to ndings made in human interventions, numerous animal studies reported bene ts of blueberries alone or mixed with other berries on weight management (42)(43)(44), markers of glucose/insulin resistance or sensitivity (10,(42)(43)(44)(45)(46), lipid pro le (42,47,48), vascular health (49,50), kidney function (51) or in ammatory markers (10,(42)(43)(44)(50)(51)(52)(53). Results from studies assessing other MetS phenotype parameters have been consistent with our ndings overall.…”
Section: Discussionsupporting
confidence: 87%
“… 7 , 8 For example, in high fat diet-induced obese mice, blueberry supplement significantly elevated insulin sensitivity and glucose tolerance and showed protective effects on pancreatic β-cells. 9 Anthocyanin-rich blueberry consumption showed beneficial effects on glycemic control in T2D patients. 10 The mulberry anthocyanin extract regulated glucose metabolism through promoting glycogen synthesis and reducing gluconeogenesis in human HepG2 cells and markedly ameliorated insulin resistance (IR) in diabetic ob/ob mice.…”
Section: Introductionmentioning
confidence: 99%
“…We could not directly compare the efficacy of hydrolyzed SF activity on promoting the regeneration of the pancreatic β-cell with the other natural compounds. When indirectly comparing the activity using the histological analysis, the efficacy of hydrolyzed SF might be expected to be similar or higher than the other natural compounds [ 25 , 26 , 27 , 28 ]. In our RT-PCR results, it was shown that the hydrolyzed SF treatment increased the gene expression of somatostatin in isolated pancreatic islets; these results suggest that hydrolyzed SF might promote not only the regeneration of pancreatic β-cell but also that of other endocrine cells in the pancreatic islets.…”
Section: Discussionmentioning
confidence: 99%